PENGARUH KOMSUMSI PISANG AMBON (Musa Acuminata Cavendish) TERHADAP PERUBAHAN TEKANAN DARAH PENDERITA HIPERTENSI PADA LANJUT USIA DI BOYOLALI: The Effect Of Ambon Banana Toward The Blood Pressure On Elderly At Boyolali - Sahuri Teguh Kurniawan; Saelan; Galih Setia Adi; Innez Karunia Mustikarani (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2022)
Blood pressure could be defined as an arterial blood vessel abnormality. Hypertension was a blood vessel system disorder characterized by an increase in blood pressure and could cause various diseases such as stroke, heart disease, and even death. Non-pharmacological effort that can be appied to control the blood pressure was by consuming Ambon banana. This study aimed to determine the effect of Ambon banana toward the blood pressure on the elderly at Boyolali. This study applied a quasy experimental research design with an approach of a pre post test with control group design. This research was conducted at Posbindu Sumber Sehat, Banyudono, Boyolali. The sampling technique used was non probability sampling with a total sampling approach. There were 30 respondents as the samples of this study consisting of 15in intervention group and 15 in control groups. The data analysis applied the Wilcoxon test because the data were not normally distributed and to find out the difference between the intervention group and the control group, it used Mann Whitney test. The Wilcoxon test results showed a change in the blood pressure on the pre-test and post-test in the intervention group with a p value of 0.001 and the results of the Mann Whitney test indicated that there was no significant difference in the intervention group and the control group with a value of 0.000. This study, there was an effect of Ambon banana on toward the blood pressure on the elderly at Boyolali